Caso radiológico - Nascimento,João Miguel (2012)
We present a case of a four year-old child with a second episode of iron deficiency anaemia. Following fever, cough and hemoptysis a chest X-ray and chest CT were performed. Bilateral and patchy areas of ground glass and consolidation were noted in the setting of intrapulmonary hemorrhage. The final diagnosis was idiopathic pulmonary hemosiderosi